Peningkatan Produktifitas Usaha Keripik Singkong Melalui Pendampingan Teknologi di Desa Geneng Kabupaten Jepara - Muhammad Abid Birrul Jabbar Shobir; Decky Rochmanto; Ahmad Ainur Rifqi; Dawam Khusnu Chuluq; Fery Irawan; Linda Yuliana; Melina Indah Susanti Azzahro; Muhammad Andriyan Saputra; Muthmainatus Tsaniah; Nita Lutfiana; Siti Yulia Zusnita (Khaira Ummah, 2022)
Cassava chips are one of the snacks favored by residents because of their crunchy texture and can be enjoyed in any circumstances while relaxing. However, most cassava chips entrepreneurs still use packaging that is fairly monotonous and old-fashioned so that cassava chips are mostly only enjoyed by the elderly. This was also experienced by the partners chosen by the Geneng Village Community Service Team. The packaging used by partners is still in the form of clear plastic with a piece of paper inside that says "Taqiya Chips". In addition to packaging that is still ancient, marketing can also be said to be still in a limited reach, namely only in shops around the production site. This is what underlies the Geneng Village Community Service Team to serve these partners. The method that the author uses in this research is Community-Based Research where the author involves partners as work partners. The method used in this community service activity is Asset Based Community Development (ABCD) where this method utilizes the assets and potentials around them. The owner of Taqiya Chips has the potential to make a product from his private garden which becomes a chip product that can be sold. The problems faced are packaging that is still monotonous and unattractive, logos that are only in the form of writing, and marketing targets that are still narrow. The KKN team provided an innovation for branding Taqiya Chips. Then carry out packaging updates and create a logo with a new design appearance, then do product marketing that will be branded through Shopee, Instagram and Tokopedia, then the products will start to be distributed.